Enhancing photosynthesis in plants: the light reactions - Cardona,T; Shao,S; Nixon,PJ (Essays in Biochemistry, 2018)
In this review, we highlight recent research and current ideas on how to improve the efficiency of the light reactions of photosynthesis in crops. We note that the efficiency of photosynthesis is a balance between how much energy is used for growth and the energy wasted or spent protecting the photosynthetic machinery from photodamage. There are reasons to be optimistic about enhancing photosynthetic efficiency, but many appealing ideas are still on the drawing board. It is envisioned that the crops of the future will be extensively genetically modified to tailor them to specific natural or artificial environmental conditions.